If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2) * 3x = 2(x + 1) + 1 Reorder the terms: 2(2 + x) * 3x = 2(x + 1) + 1 Reorder the terms for easier multiplication: 2 * 3x(2 + x) = 2(x + 1) + 1 Multiply 2 * 3 6x(2 + x) = 2(x + 1) + 1 (2 * 6x + x * 6x) = 2(x + 1) + 1 (12x + 6x2) = 2(x + 1) + 1 Reorder the terms: 12x + 6x2 = 2(1 + x) + 1 12x + 6x2 = (1 * 2 + x * 2) + 1 12x + 6x2 = (2 + 2x) + 1 Reorder the terms: 12x + 6x2 = 2 + 1 + 2x Combine like terms: 2 + 1 = 3 12x + 6x2 = 3 + 2x Solving 12x + 6x2 = 3 + 2x Solving for variable 'x'. Reorder the terms: -3 + 12x + -2x + 6x2 = 3 + 2x + -3 + -2x Combine like terms: 12x + -2x = 10x -3 + 10x + 6x2 = 3 + 2x + -3 + -2x Reorder the terms: -3 + 10x + 6x2 = 3 + -3 + 2x + -2x Combine like terms: 3 + -3 = 0 -3 + 10x + 6x2 = 0 + 2x + -2x -3 + 10x + 6x2 = 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 10x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -0.5 + 1.666666667x + x2 = 0 Move the constant term to the right: Add '0.5' to each side of the equation. -0.5 + 1.666666667x + 0.5 + x2 = 0 + 0.5 Reorder the terms: -0.5 + 0.5 + 1.666666667x + x2 = 0 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + 1.666666667x + x2 = 0 + 0.5 1.666666667x + x2 = 0 + 0.5 Combine like terms: 0 + 0.5 = 0.5 1.666666667x + x2 = 0.5 The x term is 1.666666667x. Take half its coefficient (0.8333333335). Square it (0.6944444447) and add it to both sides. Add '0.6944444447' to each side of the equation. 1.666666667x + 0.6944444447 + x2 = 0.5 + 0.6944444447 Reorder the terms: 0.6944444447 + 1.666666667x + x2 = 0.5 + 0.6944444447 Combine like terms: 0.5 + 0.6944444447 = 1.1944444447 0.6944444447 + 1.666666667x + x2 = 1.1944444447 Factor a perfect square on the left side: (x + 0.8333333335)(x + 0.8333333335) = 1.1944444447 Calculate the square root of the right side: 1.092906421 Break this problem into two subproblems by setting (x + 0.8333333335) equal to 1.092906421 and -1.092906421.Subproblem 1
x + 0.8333333335 = 1.092906421 Simplifying x + 0.8333333335 = 1.092906421 Reorder the terms: 0.8333333335 + x = 1.092906421 Solving 0.8333333335 + x = 1.092906421 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = 1.092906421 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = 1.092906421 + -0.8333333335 x = 1.092906421 + -0.8333333335 Combine like terms: 1.092906421 + -0.8333333335 = 0.2595730875 x = 0.2595730875 Simplifying x = 0.2595730875Subproblem 2
x + 0.8333333335 = -1.092906421 Simplifying x + 0.8333333335 = -1.092906421 Reorder the terms: 0.8333333335 + x = -1.092906421 Solving 0.8333333335 + x = -1.092906421 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = -1.092906421 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = -1.092906421 + -0.8333333335 x = -1.092906421 + -0.8333333335 Combine like terms: -1.092906421 + -0.8333333335 = -1.9262397545 x = -1.9262397545 Simplifying x = -1.9262397545Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.2595730875, -1.9262397545}
| 2[2(3-5x)+4]=5[2(3-3)+2] | | 30-5(6x+5)= | | 1-6x=6-x | | -4(2x+11)=11 | | 2x+45=x-5 | | x^3+7x^2-9x=63 | | x^2+27x+6=0 | | y^2+18y+13=-4 | | -2(y+3)=2y+3 | | x/2+16=77 | | 2(4+4r)+3r=63 | | y^3-7y^2+10=0 | | c/2+16=77 | | 3d-24-5=9b+18+1 | | 2(4+4r)+3=63 | | 7n^2-14n+54=-5 | | 13+17y-3(y+11)= | | 5n+3=9 | | -7=-11+x/5 | | -t+2=10 | | 6y-9y=-16-20 | | 5b^2=-12 | | 55-40=30 | | -8x-2-9x-1=4 | | 14x+13-8x-1= | | 10=1x+2 | | (3x^2-3x-2)+(3x^2+4x-3)= | | 2(3-4k)=-51+3k | | 3(3x-2)-13=4x-4 | | 10+2x+2x+x=3000 | | 3+3+(2d-5)+(2d-5)=2+2+(2d-4)+(2d-4) | | 14-3x+7=76 |